Gaya Bahasa dalam Puisi “Lautan Waktu” Karya Sanusi Pane - RR. Nindya Aurellia Nugroho (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
This study discusses the use of language style in the poem "Lautan Waktu" (The Ocean of Time) by Sanusi Pane. This language style enriches the meaning of the poem, reflecting the poet's inner struggle with time and life. Language, as a means of communication, not only functions to convey ideas and feelings but also serves as a tool for creating profound literary works, such as poetry. In this poem, Sanusi Pane employs various language styles, including personification, metaphor and exaggeration to amplify the message and evoke strong emotions. This study's objective is to examine and characterize the linguistic patterns found in Sanusi Pane's poem Lautan Waktu. Quotations from the poem are the main source of data for the qualitative descriptive analysis research approach. Metaphor is the most common language style, followed by personification and exaggeration, according to the analysis's findings. It is anticipated that this research will raise readers' awareness of language use so they may comprehend literary works more thoroughly.